A teoria do realinhamento eleitoral no Brasil: apropriações e hipóteses - Lage, Daniel [UNIFESP] (2016)
This work focuses on the theory of electoral realignment comprehending it as powerful lens for analysis of democratic processes in the long term. The present work starts with a study of the origins and development of such theory in the United States, followed by the analysis of its use in Brazil, reviewing and mapping the adaptation demands of the theory to the brazilian reality. Instead of the idea of an electoral realignment in the 2006 presidential election, it is hypothesized an electoral alignment as a important consolidation moment of the relation between party and social base in the young brazilian democracy - wich should be conserdered before the possibility of realignment itself. Therefrom, this study try to find a long-term interpretive scheme for the period 2002 to 2014. The notion of strategic interaction between the voter's choice and the choice of the parties in elections take place in the center of the analytical model. Thus, the hypothesis of alignment sum up with the class reconciliation experience held in PT governments, characterizing a particular experience of social democracy.